A retrospective comparison of outcome and toxicity of preoperative image-guided intensity-modulated radiotherapy versus conventional pelvic radiotherapy for locally advanced rectal carcinoma. (13th October 2016) - Huang, Chun-Ming; Huang, Ming-Yii; Tsai, Hsiang-Lin; Huang, Ching-Wen; Ma, Cheng-Jen; Lin, Chih-Hung; Huang, Chih-Jen; Wang, Jaw-Yuan
Abstract: The aim of the study was to compare clinical outcomes and toxicity between 3D conformal radiotherapy (3DCRT) and image-guided intensity-modulated radiotherapy (IG-IMRT) administered through helical tomotherapy in locally advanced rectal cancer (LARC) patients receiving preoperative chemoradiotherapy. We reviewed 144 patients with Stage II–III rectal cancer receiving preoperative fluoropyrimidine-based chemoradiotherapy followed by radical resection. Tumor responses following chemoradiotherapy were evaluated using the Dworak tumor regression grade (TRG). Of the 144 patients, 45 received IG-IMRT and 99 received 3DCRT. A significant reduction in Grade 3 or 4 acute gastrointestinal toxicity (IG-IMRT, 6.7%; 3DCRT, 15.1%; P = 0.039) was observed by IG-IMRT. The pathologic complete response (pCR) rate did not differ between the IG-IMRT and the 3DCRT group (17.8% vs 15.1%, P = 0.52). Patients in the IG-IMRT group had the trend of favorable tumor regressions (TRG 3 or 4) compared with those in the 3DCRT group (66.7% vs 43.5%, P = 0.071). The median follow-up was 53 months (range, 18–95 months) in the 3DCRT group and 43 months (range, 17–69 months) in the IG-IMRT group. Four-year overall, disease-free, and local failure–free survival rates of the IG-IMRT and 3DCRT groups were 81.6% and 67.9% ( P = 0.12), 53.8% and 51.8% ( P = 0.51), and 88% and 75.1% ( P = 0.031), respectively. LARC patients treated with preoperative IG-IMRT achieved lower acute gastrointestinal adverse effects and a higher local control rate than those treated with 3DCRT, but there was no prominent difference in distant metastasis rate and overall survival between two treatment modalities.